1993
DOI: 10.1093/nar/21.16.3705
|View full text |Cite
|
Sign up to set email alerts
|

The different binding modes of Hoechst 33258 to DNA studied by electirc linear dichroism

Abstract: The binding mode of the bisbenzimidazole derivative Hoechst 33258 to a series of DNAs and polynucleotides has been investigated by electric linear dichroism. Positive reduced dichroisms were measured for the poly(dA-dT).poly(dA-dT)- and poly(dA).poly(dT)-Hoechst complexes in agreement with a deep penetration of the drug into the minor groove. Similarly, the drug displays positive reduced dichroism in the presence of the DNAs from calf thymus, Clostridium perfringens and Coliphage T4. Conversely, negative reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 26 publications
9
73
0
Order By: Relevance
“…Figures 5 and 6), which reflects an orientation of the phenanthridine chromophore more or less coplanar to the plane of polynucleotide basepairs could be attributed to intercalation between basepairs. 37 However, at conditions of an excess of 5, 6 over intercalative binding sites ( r[5,6]/ [dGdC]  0.2) stronger negative ICD bands appear accompanied by systematic deviation from the isoelliptic points, which suggests agglomeration of 5, 6 along DNA. Addition of 6 induced changes in CD spectra of ctDNA (composition 58% AT, 42% GC) similar to those with ATpolynucleotides (the increase of CD spectra in the 260-290 region and strong positive ICD at   290 nm) at both, pH 5.0 and pH 7.0.…”
Section: Circular Dichroism Experimentsmentioning
confidence: 99%
“…Figures 5 and 6), which reflects an orientation of the phenanthridine chromophore more or less coplanar to the plane of polynucleotide basepairs could be attributed to intercalation between basepairs. 37 However, at conditions of an excess of 5, 6 over intercalative binding sites ( r[5,6]/ [dGdC]  0.2) stronger negative ICD bands appear accompanied by systematic deviation from the isoelliptic points, which suggests agglomeration of 5, 6 along DNA. Addition of 6 induced changes in CD spectra of ctDNA (composition 58% AT, 42% GC) similar to those with ATpolynucleotides (the increase of CD spectra in the 260-290 region and strong positive ICD at   290 nm) at both, pH 5.0 and pH 7.0.…”
Section: Circular Dichroism Experimentsmentioning
confidence: 99%
“…5,6) It has been suggested that the 2-amino group of guanine protruding in the minor groove may prevent Hoechst 33258 from getting access to the minor groove of GC sequences. If so, the second binding mode of this drug, which would occur after the first stage binding at AT rich sequences has finished, may take place at GC rich sequences.…”
Section: )mentioning
confidence: 99%
“…3) The spectroscopic characteristics of Hoechst 33258 family of ligands have brought them into wide use as DNA fluorophores, 5) but several have also shown potent activity against a number of microorganisms that lead to AIDS-related opportunistic infections, 6) as well as exhibiting cytotoxic activity. [7][8][9][10] In the course of our investigations of minor groove binding drugs, we reported a cytotoxicity and DNA-binding ability of carbamate derivatives of Hoechst 33258 with chloroalkyl and bromoalkyl moieties (Fig.…”
mentioning
confidence: 99%